EXPERIENCE IN THE TREATMENT OF SUBAPONEUROTIC ACCUMULATION OF CEREBROSPINAL FLUID IN AN INFANT (CLINICAL CASE) - Игорь Иванович Ларькин; Елена Николаевна Кравченко; Валерий Иванович Ларькин (The Publishing House Medicine and Enlightenment, 2022)
Currently, there is no single explanation for the occurrence of subaponeurotic accumulations of cerebrospinal fluid in infants [1, 2]. In the Russian literature, this pathology is described as «epidural-subcostal hematomas» or hemoliquoromas [3]. The main part of the authors among the causes of such clusters indicates the use of vacuum extraction performed for progressive fetal hypoxia. At the same time, there are isolated reports of the diagnosis of such clusters after cesarean section, and even physiological childbirth [4]. The opinion of researchers regarding therapeutic tactics does not coincide. Puncture of a liquid subaponeurotic formation is an element of diagnosis and treatment, but after puncture, cerebrospinal fluid often accumulates again [5]. We present a clinical observation of spontaneous cerebrospinal fluid accumulation in a child of 2 months. The child was observed after childbirth by a district pediatrician with a diagnosis of «cephalohematoma», but due to the duration of the course of the disease, he was sent for consultation to a neurosurgeon. Spontaneous cerebrospinal fluid accumulation was suspected, puncture removal of the latter was performed. In the next day, a procedure was diagnosed. The parents refused to repeat the puncture. Compression bandages were used for treatment, and spontaneous resorption of the formation was detected after 3 weeks. The rarity of this pathology, the need to develop optimal treatment tactics explains the relevance of the message.